Simulasi Transaksi Pembayaran Online dengan Studi Kasus Kantin Universitas Kristen Petra - Hanny Tabita Listyani; Andreas Handojo; Henry Novianus Palit (Jurnal Infra, 2018)
The transaction is an activity that causes changes to the financial position, the transaction is said to be valid or valid, if completed with proof of transaction. During this time, the transaction process that took place in Petra Christian University Canteen was done manually, i.e. students or employees ordered food to the booths. This resulted in slow transaction transactions and hassle booths, and did not deny the possibility of loss of proof of sale transaction, proving that the transaction is valid / valid.To answer the problem, designed a system that utilizes RFID technology (Radio Frequency Identification). By utilizing this technology, students and employees can use identity cards (KTM / Employee Card) in conducting transactions in the canteen. In addition to transactions to be safe because it is done digitally, it can help buy-sell transactions to be faster. In addition, the PetraCanteen Application is intended for employees, includinglecturers who want to conduct transactions online, so no longer need to queue in the canteen, or make phone calls to the cafeteria.